2021
DOI: 10.1088/1757-899x/1053/1/012080
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Hazard Analysis and Critical Point (HACCP): A Case of Lumpia Semarang

Abstract: Indonesia is a country rich in diversity of food types. One of them is Lumpia, which is a typical Semarang food. In this study, the analysis of HACCP in the production of Lumpia has comprehensively explained. The writing method used is a literature review and visualization of information from various types of literature. The analysis carried out in this study consists of 2 steps, namely the analysis of potential hazards and the implementation phase of HACCP, which consists of forming a HACCP team with internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Bhaskarachry et al [24] and Harasym et al [25] explore the relationship and development of local foods and functional foods. Suherman et al [26] identified Hazard Analysis and Critical Point (HACCP) Semarang-typical local food, lumpia (spring roll). According to several of these studies, research on HCP for functional local foods has not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Bhaskarachry et al [24] and Harasym et al [25] explore the relationship and development of local foods and functional foods. Suherman et al [26] identified Hazard Analysis and Critical Point (HACCP) Semarang-typical local food, lumpia (spring roll). According to several of these studies, research on HCP for functional local foods has not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%